Разложить на множители 1) x^6-x^4-x^2+1

nastyyya4 nastyyya4    2   16.09.2019 12:00    0

Ответы
Liana03102000 Liana03102000  10.09.2020 10:15
X⁶ - x⁴ - x² + 1 = (x⁶ - x²) - (x⁴ - 1) = x²(x⁴ - 1) - (x⁴ - 1) =
= (x⁴ - 1)(x² - 1) = (x² - 1)(x² + 1)(x² - 1) = (x - 1)(x + 1)(x² + 1)(x - 1)(x + 1) =
= (x - 1)²(x + 1)²(x² + 1)

Разложить на множители 1) x^6-x^4-x^2+1
ПОКАЗАТЬ ОТВЕТЫ
yakubchik2004 yakubchik2004  10.09.2020 10:15
Ну вот так как-то получается
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра